The Threshold : The Rhetoric of Historiography in Early Medieval China - Raft, Zeb (Harvard University Asia Center, 2023)
What happens when historiography-the way historical events are committed to writing-shapes historical events as they occur? How do we read biography when it is truly "life-writing," its subjects fully engaged with the historiographical rhetoric that would record their words and deeds? See Less